2016
DOI: 10.4172/1948-5948.1000331
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Levels of the Mutagenic, Carcinogenic Hydroxylated Aflatoxins (AFM1 and AFM2) in Artisanal Oaxaca-Type Cheeses from the City of Veracruz, Mexico

Abstract: Microbial & Biochemical Technology J o u rn al of M ic ro b ia l & Bioc h e m ic a l Te chno lo g y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…AFM2 is also another metabolite of hydroxylation of AFB2 but is of little concern as compared to AFM1. Hernandez-Camarillo et al [78] reported an occurrence of AFM2 in 20% of cheese in Mexico (mean 0.2 µg/kg) in comparison with 53% reported for AFM1 (mean 3.0 µg/kg) in the same samples [78]. With the higher occurrence of AFB1 in dairy feed in comparison with AFB2 in SSA, AFM1 is therefore of major concern as compared to AFM2.…”
Section: Food Safety and Hazards Of Mycotoxinsmentioning
confidence: 96%
“…AFM2 is also another metabolite of hydroxylation of AFB2 but is of little concern as compared to AFM1. Hernandez-Camarillo et al [78] reported an occurrence of AFM2 in 20% of cheese in Mexico (mean 0.2 µg/kg) in comparison with 53% reported for AFM1 (mean 3.0 µg/kg) in the same samples [78]. With the higher occurrence of AFB1 in dairy feed in comparison with AFB2 in SSA, AFM1 is therefore of major concern as compared to AFM2.…”
Section: Food Safety and Hazards Of Mycotoxinsmentioning
confidence: 96%
“…A report of artisanal Oaxaca fresh cheese from the State of Veracruz, Mexico, examined AFM 1 and AFM 2 in 30 samples, with 16/30 (53%) having AFM 1 contamination (0.01 to 44 µg kg -1 ). AFM 2 was less frequent, present only in 6/30 (20%), with a concentration range between 0.67 and 3.43 µg kg -1 [28].…”
Section: Aflatoxins In Milk and Cheeses In Mexico And Worldwidementioning
confidence: 94%
“…AFs have been identified in raw and pasteurized milk in Brazil, Turkey, Kuwait, Italy, Serbia [21][22][23] and Australia [24]. There are reports of AFs (AFB 1 , AFM 1 and AFL) in 580 L of Mexican milk, where 13% of pasteurized and 8% of ultrapasteurized milk with different amounts of fat contained AFL (>0.05 µg L -1 ) [25,26] and AFL was also found in artisanal Oaxaca cheese in Veracruz, Mexico [27,28]. There were only traces of AFB 1 (0 a 0.4 µg/L), and the amount of fat was not significant.…”
Section: Aflatoxins In Milk and Cheeses In Mexico And Worldwidementioning
confidence: 99%
“…International agency for research on cancer (IARC) categorized AFB1 as Group I of carcinogen and AFM1 as Group 2B of carcinogenic compounds [1,7]. AFB1 is thought to be the most potent toxic aflatoxin and metabolically produces the monohydroxy derivative AFM1 [8,9,10]. AFM1 is almost as acutely toxic as AFB1, while its mutagenic and carcinogenic potential seems to be lower [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…AFB1 is thought to be the most potent toxic aflatoxin and metabolically produces the monohydroxy derivative AFM1 [8,9,10]. AFM1 is almost as acutely toxic as AFB1, while its mutagenic and carcinogenic potential seems to be lower [11,12,13].…”
Section: Introductionmentioning
confidence: 99%